Answer:
The fourth option is the correct answer
Step-by-step explanation:
The given expression is
-2n(5+n-8-3n)
Given that n=3,We substitute the value of n into the expression and simplify.
This implies that,
-2n(5+n-8-3n)=-2(3)[5+3-8-3(3)]
=-6(5+3-8-9)
=-6(-9)
=54
Hence the answer is 54
Answer: 122 sq. in.
Step-by-step explanation:
P = 2 (l + w)
P = 2 (34.5 + 26.5)
P = 2 x 61
P = 122 sq. in. = 0.847 sq ft = 0.0941 sq. yards
Perform indicated multiplication:
11c+3(-5c)+3(4d)
11c-15c+12d combine like terms
(11c-15c)+12d
-4c+12d factor
4(3d-c)
Answer:
1. subtract 9 from z- z-9
2. add 9 and z - z+9
3. divide 9 by z - 9/z
4. multiply 9 by z - 9z
Step-by-step explanation:
Your welcome!
Brainliest Appreciated!